Can easing financial constraints reduce carbon emissions? Evidence from a large sample of French companies - Mattia Guerini; Giovanni Marin; Francesco Vona (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
We study how monetary policy shapes firm-level carbon emissions by exploiting the ECB's 2012 entry into the zero lower bound as a plausibly exogenous credit easing. Using administrative and survey data on French manufacturing firms from 2000-2019 and a difference-in-differences design with debt-to-asset ratios as exposure, we show that financially constrained firms cut emissions 9.4% more than unconstrained ones, primarily through lower energy intensity and capital-deepening productivity gains. Small and medium enterprises drive the results. Aggregating our estimates implies average annual reductions of 3.3%, amounting to 5.3 million tonnes of CO₂ saved.
Keywords: Q52; Q48; D22; 330; Financial constraints; credit supply; firm-level carbon emissions; climate policies